HAMBATAN KOMUNIKASI ANTARBUDAYA AWARDEE IISMA PADA UNIVERSITAT POMPEU FABRA DI NEGARA SPANYOL - Ananda Govinda (2023)
Indonesian International Student Mobility Awards (IISMA) is one of the programs from the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) in developing Indonesian students' insight to global knowledge and international culture through abroad studies to various countries, one of which is Spain. Universitat Pompeu Fabra as one of IISMA Host Universities in Spain is an international standard university. It is also influenced by Barcelona as a city which helds a strong local culture, but also intensely exposed to international culture. IISMA Awardees who study for 1 semester at their designation are required to adapt new cultures and faces certain forms of intercultural communication barriers. Aside from the differences in language, the intercultural communication barriers may also come from differences in society, norms and habits, and individual perceptions. This research is conducted with the purpose of analyzing the forms of intercultural communication barriers experienced by IISMA Awardees at Universitat Pompeu Fabra during their studies in Spain through aspects of intercultural communication barriers according to Liliweri (2013). This study will also analyze the Awardees' perception over experiencing forms of intercultural communication barriers through the Gudykunst & Kim's (1997) model of intercultural communication and also the concept of identity, as well as their solutions in overcoming these barriers through the Kim's (2001) concept of adaptation. The result of this research proves that Awardees are facing various intercultural communication barriers, the correlation between Awardees' personal identity to perception of the occurring intercultural communication barriers, as well as efforts by Awardees done as a part of their adaptation process.